Penerapan Nilai-Nilai Syariah dalam Sistem Pembayaran Nontunai (E-Wallet) di Kalangan Generasi Z Muslim - Chairina Amaliah Hasibuan; Cindy Amelia; Suci Ramadani Harahap; Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of financial technology has brought various innovations in payment systems, especially e-wallets which are increasingly popular among young generations. This article examines the application of sharia values in the use of e-wallets by Muslim Generation Z in Indonesia. Through a qualitative approach with in-depth interview methods with Muslim Generation Z e-wallet users, this research explores understanding, perceptions, and practices of using e-wallets from a sharia perspective. The research results show that the majority of respondents have awareness of the importance of compliance of financial products with Islamic values, but in-depth understanding of sharia aspects in e-wallets is still limited. It was found that factors of convenience, promotions, and transaction speed are more dominant in influencing e-wallet choices compared to sharia considerations. These findings indicate the need for increasing digital sharia financial literacy and developing e-wallet features that more explicitly apply sharia principles to meet the needs of the growing young Muslim market.